Bone Metabolism and Fracture Risk in Diabetes Mellitus - Puspitasari, Melisa Diah; Purnamasari, Dyah; Setyohadi, Bambang; Isbagio, Harry (Journal of the ASEAN Federation of Endocrine Societies, 2017)
Individuals with type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) are at increased risk for fragility fractures. Bone mineral density (BMD) is decreased in T1DM but often normal or even elevated in T2DM when compared with age-matched non-DM populations. However, bone turnover is decreased in both T1DM and T2DM. The pathophysiologic mechanisms leading to bone fragility is multifactorial, and potentially leads to reduced bone formation, altered bone microstructure and decreased bone strength. Interestingly, different antidiabetic treatments may influence fracture risk due to effects on glycemic control, triggering of hypoglycemic events or osteoblastogenesis.